Randomized phase II study of weekly paclitaxel versus paclitaxel and carboplatin as second-line therapy in disseminated melanoma: a multicentre trial of the Dermatologic Co-operative Oncology Group (DeCOG) - Zimpfer, Christine; Figl, Robert; Schadendorf, Dirk (Melanoma research, 2003)
Stage melanoma IV has a poor prognosis, with a median survival time between 3 and 11 months from the diagnosis of distant metastases. Response rates in first-line regimens are around 20%. To date, no second-line treatment has been established. We performed a randomized, multicentre, second-line clinical phase II study of paclitaxel either as monotherapy or combined with carboplatin given on an outpatient basis. In arm A, paclitaxel was administered at a dose of 100 mg/m2 intravenously on day 1 each week for 6 weeks. In arm B, paclitaxel was administered at a dose of 80 mg/m2 intravenously followed by carboplatin 200 mg/m2 on day 1 each week for 6 weeks. The next cycle was administered after a 2 week intermission. The response rate, survival time, time-to-progression and toxicity were assessed in both arms. The study was stopped after 40 patients because the overall response rate was below 10% in both arms. The median survival time after initiation of second-line treatment was 209 days (± 196 days) for patients treated with paclitaxel only, and 218 days for those treated with paclitaxel/carboplatin. The median time-to-progression was around 56 days in both arms. Two partial responses were observed after 16 weeks, lasting for 8 and 12 weeks, respectively. Although both treatment modalities were well tolerated, haematological toxicity was higher in the combination arm. This is so far the largest second-line clinical phase II study reported in melanoma. However, paclitaxel with or without carboplatin had only limited efficacy, and the combination of these drugs adds significantly to haematological toxicity without improving response or survival rates.
Gesehen am 25.11.2020